THE INFLUENCE OF TRADITIONAL AND NON-TRADITIONAL MUSICAL AND PLAY ACTIVITIES ON CHILDREN'S DEVELOPMENT - Konurova Leyla Ruslanovna (Scholar Express Journal, 2025)
This study analyzes the influence of traditional and non-traditional musical and play activities on the development of preschool children. In recent decades, musical and play activities in the preschool education system have become increasingly important, as they contribute to the harmonious development of children, developing their emotional, cognitive, social and creative spheres. Traditional forms of musical and playful activities, such as singing, playing musical instruments, dancing and round dances, are aimed at developing musical abilities, a sense of rhythm and social interaction. At the same time, non-traditional approaches, including improvisation, the use of non-standard musical instruments, and digital technologies, create new opportunities for self-expression, creativity and flexibility of thinking in children. Thus, the integration of traditional and non-traditional forms of musical and play activities is the most effective strategy for the comprehensive development of preschool children, since it covers both traditional and innovative approaches in the educational process aimed at developing the creative, social and cognitive abilities of children
Keywords: traditional musical and play activities; non-traditional musical and play activities; preschool education